Effect of mobile guided cardiac rehabilitation on quality of life – the EU-CaRE randomised clinical trial. (25th November 2020) - Houben, V; Snoek, J.A; Prescott, E; Mikkelsen, N; Van Der Velde, A.E; Eijsvogels, T.H.M; Prins, L.F; Kolkman, E; Meindersma, E; Gonzales-Juanatey, J.R; Pena-Gil, C; Ilou, M.C; et al.
Abstract: Background and purpose: Although participation in cardiac rehabilitation (CR) improves quality of life (QoL), participation in CR, especially among elderly, is limited. We conducted this study to assess whether mobile home-based CR (mCR) increases QoL in elderly (≥65 years old) patients with coronary artery disease (CAD) or a valvular intervention who decline participation in conventional CR. Methods: It is designed as a randomised multi-centre study with two parallel arms. Randomisation assigned patients either to mCR or a control group. mCR Consisted of six months of home-based CR with telemonitoring and coaching. Control-group patients did not receive any form of CR throughout the study period. Quality of life was measured with the SF-36v2 questionnaire at 0, 6 and 12 months. Results: A total of 179 patients were included in this study (90 control, 89 mCR). A flowchart of the trial is presented in Figure 1. Patients were predominantly male (81.1%). Baseline characteristics can be found in Table 1. Patients using mCR improved on physical QoL after 6 (p=0.026) and 12 (p=0.008) months. There was no difference on mental QoL for both groups (mCR 6 months p=0.563, 12 months p=0.945; control 6 months p=0.589, 12 months p=0.542). No difference existed in QoL between the mCR and control group (physical: 6 months p=0.070, 12 months p=0.150; mental: 6 months p=0.355, 12 months p=0.625). Conclusion: Although there is no significant difference in QoL between the control and mCR group, mCR increases physical QoL after 6 and 12 months in elderly patients who decline participation in conventional CR. Therefore E-Health tools should be considered as an alternative for conventional CR when (elderly) patients decline to participate in conventional CR. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): European Union's Horizon 2020 research and innovation programme